Delayed Impairment of Postural, Physical, and Muscular Functions Following Downhill Compared to Level Walking in Older People - Hill, Mathew William; Hosseini, Edyah-Ariella; McLellan, Abbie; Price, Michael James; Lord, Stephen Ronald; Kay, Anthony David (Frontiers in Physiology, 2020)
Transient symptoms of muscle damage emanating from unaccustomed eccentric exercise can adversely affect muscle function and potentially increase the risk of falling for several days. Therefore, the aims of the present study were to investigate the shorter- and longer-lasting temporal characteristics of muscle fatigue and damage induced by level (i.e. concentrically-biased contractions) or downhill (i.e. eccentrically-biased contractions) walking on postural, physical and muscular functions in older people. Nineteen participants were matched in pairs for sex, age and self-selected walking speed and allocated to a level (n = 10, age = 72.3 ± 2.9 years) or downhill (n = 9, age = 72.1 ± 2.2 years) walking group. Postural sway, muscle torque and power, physical function (5 × and 60 s sit-to-stand) and mobility (Timed-Up-and-Go [TUG]) were evaluated at baseline (pre-exercise), 1 min, 15 min, 30 min, 24 h and 48 h after 30 min of level (0% gradient) or downhill (−10% gradient) walking on a treadmill. Following downhill walking, postural sway ( +66 to 256%), TUG (+29%), 60 s sit-to-stand (+29%), 5 times sit-to-stand (−25%) and concentric power (−33%) did not change at 1-30 min post exercise, but were significantly different (p < 0.05)at 24 h and48 h post-exercise when compared to baseline (p < 0.05). Muscle torque decreased immediately after downhill walking and remained impaired at 48 h post-exercise (−27 to −38%). Immediately following level walking there was an increase in postural sway (+52 to +98%), slower TUG performance (+29%), fewer sit-to-stand cycles in 60 s (−23%), slower time to reach 5 sit-to-stand cycles (+20%) and impaired muscle torque (−23%) and power (−19%) which returned to baseline 30-min after exercise cessation (p > 0.05). These findings have established for the first time distinct impairment profiles between concentric and eccentric exercise. Muscle damage emanating from eccentrically-biased exercise can lead to muscle weakness, postural instability and impaired physical function persisting for several days, possibly endangering older adult’s safety during activities of daily living by increasing the risk of falls.